(untitled) (Economic studies journal, 2023)
The current research analyses the impact of bank credit in economic growth in Libya over the period 1970 – 2022, co-integration approach was adopted in this research by using Engel-Granger method and causality Granger. The research resulted that there is no relationship in the long term between bank credit and economic growth. The causality Granger indicated that there is a positive bidirectional between the two variables in the short term.